Transcutaneous Bilirubin Measurements Can Be Used to Measure Bilirubin Levels during Phototherapy - Saad Abdullah Alsaedi (Hindawi Limited, 2018)
Objective. To determine whether transcutaneous bilirubin measurements (TcB) before and during phototherapy taken from covered skin during phototherapy correlate with total serum bilirubin (TSB) levels. Study Design. In this prospective observational study, healthy term newborns who required TSB measurements were included. TcB measurements were taken from the forehead before starting and during phototherapy using the BiliChek device. Before starting phototherapy, part of the forehead was covered. Blood for TSB measurement was collected within 5 minutes of TcB measurements. Correlations and mean differences between TcB and TSB before and during phototherapy were calculated. Result. Paired TSB and TcB measurements before and during phototherapy in 151 newborns were performed. The mean gestational age was 38.8 weeks and birth weight was 3.1 kg; 53% were male. Before starting phototherapy, TSB and TcB were 183.8±41.6 and 190.5 ± 43 μmol/l, respectively. During phototherapy, TSB and TcB were 191.8±39.4 and 187.8±45.3 μmol/l, respectively. Linear regression analysis showed a significant correlation between TcB and TSB before starting phototherapy and during phototherapy (r: 0.85; p<0.001 and r: 80.0; p<0.001), respectively. Before starting phototherapy, the mean difference between TSB and TcB was 6.2±23.2 μmol/l, with a 95% CI of −39.3 to 51.7 μmol. During phototherapy, the mean difference was −2.8±23.5 μmol/l, with a 95% CI of −48.9 to 43.3 μmol/l. Conclusion. TcB measurements from covered skin in jaundiced term infants during phototherapy correlate with TSB and can be used to monitor bilirubin levels during phototherapy.